ECONOMIC LEGAL ANALYSIS OF FREE SCHOOL MEAL PROGRAM IN INDONESIA - Imelda Mardayanti (CV. RADJA PUBLIKA, 2025)
The free meal program for school children is a government policy that aims to improve children's welfare and reduce the economic burden on families. This study analyzes the legal basis that supports the program, the economic impact on families and communities, and its implementation from the perspective of economic law. This study uses a juridical-normative and empirical approach with case studies in several regions. The results show that this program has a strong legal basis, provides significant economic benefits, but faces challenges in implementation. Policy recommendations include increasing regulations, budget transparency, and strengthening oversight mechanisms.